﻿Le tympan dans les portails flamboyants en France - Sanfaçon, Roland (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1988)
In thirteenth-century France, tympanums were the focus of interest in great portals. With their horizontal registers of reliefs and statues, they displayed major iconographic themes, while jambs and archivolts appeared to be a complementary frame. On the other hand, the multiplication of archivolts created deep recesses at the bottom of which tympanums could seem submissive to their environment.In the fifteenth century, the flamboyant style stressed both the independence of elements and their intimate interrelations. Prominent elements were mouldings of jambs, arches, and gables of doors, niches, statues, and canopies anywhere. All of them overlapped with tympanums in an intense search for liaisons. Nevertheless, surfaces of tympanums could be defended as independent elements, as they could be of any shape or proportion without regard to the forms of adjacent framing arches.Quite often, on the other hand, tympanums were rather understressed. They were just treated as true or false windows with open or blind tracery. As such, their submissive placement behind prominent jambs and buttresses must have appeared inferior. They were progressively eliminated as in some cases the tympanum was just either an ambiguous and small part of wall between two superimposed arches, or a taller window or retable above a rather independent doorway. This paved the way for the Renaissance. It marked the end of the medieval tympanum, and the end of the medieval mind as well.